The Influence of Military Logistics to the Environment of Military Areas: Social, Legal, and Ethical Aspects. Case Study from the Czech Republic - Jan Lípa; Ladislav Rozenský; Aly Hawa Camara (Studia Ecologiae et Bioethicae)
This article deals with the influence of military logistics on the environment in the districts of the Czech Republic. There were ten military districts on the territory of the Czech Republic, i.e., areas that served exclusively the needs of the defenseof the state. Currently, six of them areabolished. Other military districts, on the other hand, are still active - these are the areas of Boletice, Březina, HradištěandLibavá. Using the example of Boletice, this article shows the positive and negative effects on the environment and also considers some social and ethical questions from the perspective of the social aspect of ethics, in relation to social needs and environmentalism. In its discussion, this thesis also reflects on the need for social dialogue and environmental education of the population. Similar conditions as in Boletice, with preserved biodiversity and environment, also have other active districts. As a result, a number of protected areas and localities could be created within them. This work shows that, as a result of the past steps of the Czech policy, the districts are islands of biodiversity, and the negative effects of the training activities did not affect them to a greater extent, and that the civil workers of the districts and the residents who are adjacent to them, thanks to environmental education, have voluntarily adopted an ethical and social consensus and accepted some of the limitations that life in this place brings.